Design and Synthesis of Benzopyranopyrimidinyl Phosphonates as Cytotoxic and Antioxidant Agents - Santhisudha, Sarva; Mohan, Gundluru; Rani, Tenkayala S.; Reddy, Peddaiahgari V. G.; Reddy, Cirandur Suresh (Letters in Drug Design & Discovery, 2019)
Background: A concatenation of bioactive diethyl(2-hydroxyphenylsubstituted) benzopyrano pyrimidinyl phosphonates were synthesized under eco-friendly green conditions in the presence of palladium doped graphitic carbon nitride (Pd@g-C3N4) as catalyst. Methods: The title compounds were evaluated for cytotoxic activity against MCF-7, SW-480, HeLa and HL-7702 cell lines and in-vitro antioxidant activity by DPPH, NO and H2O2 methods. Results: The synthesized compounds manifested robust cytotoxic and antioxidant activities. Conclusion: Some of them showed much higher bioactivity than the standards.
Keywords: one-pot